Screening of Conditions for the Preparation of Poly( -Caprolactone) Nanocapsules Containing the Local Anesthetic Articaine - Campos, Estefania Vangelie Ramos; Melo, Nathalie Ferreira Silva; Paula, Eneida de; Rosa, André Henrique [UNESP]; Fraceto, Leonardo Fernandes (American Scientific Publishers, 2013)
The local anesthetic articaine (ATC) is widely used in dentistry; however, its side effects can include paresthesia and nerve injury. Polymeric nanocapsules (PN) can be used as carriers for drugs, and help to reduce undesirable symptoms. The objective of this study was to evaluate the influence of different factors on the average size, polydispersion, and encapsulation efficiency of PN containing ATC. Poly(ε-caprolactone) (PCL) nanocapsules containing ATC were prepared by the oil-in-water emulsion/solvent evaporation method. The final ATC concentration was 2%. The preparation conditions were optimized using a central composite blocked cube-star design to investigate the influence of two variables at five levels, with 22 factorial points (–1 and +1), two replicates of the central point, 2×2 axial points (–1.414 and +1.414), and an orthogonal distribution, resulting in 10 experiments. The factors varied were the PVA concentration and the sonication time. The nanocapsules showed a satisfactory size range, a polydispersivity index less than 0.2, and high encapsulation efficiency. The values of the factors had no significant influence on either average size or polydispersion, although the encapsulation efficiency was significantly influenced by the sonication time. Improved formulations were identified using the central composite design, which revealed that the main consideration in selecting a suitable formulation was the encapsulation efficiency. Two of the formulations showed both high encapsulation efficiency and colloidal characteristics appropriate for the route of administration.
Keywords: nanocapsulas; articaina; liberação controlada